IDENTIFIKASI PARAMETER DAN PERANCANGAN SISTEM KENDALI PID UNTUK ANALISIS SIKAP TERBANG UAV [PARAMETER IDENTIFICATION AND DESIGN PID CONTROLLER FOR FLYING ATTITUDE ANALYSIS OF UAV] - Purwanto, Eko Budi; Nasution, Syahron Hasbi; Supendi (BRIN Publishing, 2012)
Based on the state space yield first principle method knowed that characteristic of UAV is static stable. To get the near real condition doing verification of state space model by using the identification system toolbox of Matlab. The yield show that matrix element of state space is different both of them. Furher step is design the PID control system base on new state space, and for improve the performance system used Kalman filter.